2017
DOI: 10.1200/jco.2017.35.15_suppl.6624
|View full text |Cite
|
Sign up to set email alerts
|

Price trajectories assessment for Medicare Part B generic anti-cancer drugs.

Abstract: 6624 Background: Patented anti-cancer drugs launch prices have increased in recent years with subsequent increases after launch. Recently, large price increases of generic drugs were at the center of public attention in the United States. Our aim was to assess price changes with time for Medicare part B anti-cancer generic drugs and to understand how drug characteristics and market structure influence price trajectories. Methods: We included all Medicare part B anti-cancer drugs with price reported in both 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Two interview guides were formulated based on the literature6 7 11 12 and input from clinical cancer experts. The interview guides comprised similar non-directive and open-ended questions about perceptions, concerns, emotions and experiences with unfunded high-cost cancer therapies.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two interview guides were formulated based on the literature6 7 11 12 and input from clinical cancer experts. The interview guides comprised similar non-directive and open-ended questions about perceptions, concerns, emotions and experiences with unfunded high-cost cancer therapies.…”
Section: Methodsmentioning
confidence: 99%
“…4 Therefore, public health systems do not fund most of these treatments, the price of which can be very high and continues to increase. [5][6][7] In 2011, the USA approved innovative treatments for various cancers that cost more than US$100 000 per patient for a 1-year treatment, although only a few of these treatments prolonged patients' lives. 5 Gordon et al 6 found that around half of 31 generic drugs had significantly increased in price, while the cost of about a quarter of these drugs increased by approximately 200% between 2006 and 2016.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations